Arte Comentada 3 2020
DOI: 10.22533/at.ed.2722024073
|View full text |Cite
|
Sign up to set email alerts
|

O Que É Necessário Para Se Fazer Uma Fotografia: Percepções De Estudantes Do 5º Ano Do Ensino Fundamental

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição 4.0 Internacional (CC BY 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores, inclusive não representam necessariamente a posição oficial da Atena Editora. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The 25% increase in the purchase recurrence rate by consumers aged between 16 and 45 years is also evident (Eurostat -Statistics Explained, 2021;SAPO, 2021). In the wine market, the percentage of consumers buying online increased by 7% in 2020, a significant increase for this market (Martins, 2021). The pandemic accelerated the sale of alcoholic beverages in e-commerce and increased consumer engagement (Hora & Lanari, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 25% increase in the purchase recurrence rate by consumers aged between 16 and 45 years is also evident (Eurostat -Statistics Explained, 2021;SAPO, 2021). In the wine market, the percentage of consumers buying online increased by 7% in 2020, a significant increase for this market (Martins, 2021). The pandemic accelerated the sale of alcoholic beverages in e-commerce and increased consumer engagement (Hora & Lanari, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, currently only approximately 19% of persons in Portugal aged between 16 and 74 years shopped online for food or beverages (INE, 2020). Although the data indicated that in 2020 the percentage of consumers who purchased wine online was 7%, compared to 5% in 2019 (Martins, 2021), even though this is a small percentage of all online sales, it is significant and should be taken into account by businesses integrated into the wine sector. The data indicates that online sales are gaining more and more importance in consumer behaviour.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation